Effect of lamination on rock properties under uniaxial loading - Ooi, Chow Ern (2008)
The objective of this study is to determine the effect of lamination on rock properties under uniaxial compression loading. Rocks are often anisotropic with regard to their mechanical behaviour, and this property is usually associated with sedimentary and metamorphic rocks. The properties of such rocks vary with direction of loading. The anisotropy of sedimentary rocks such as sandstone is due to mineral arrangement and termed as lamination. Other related properties like Young’s Modulus and Poisson’s ratio also vary with respect to lamination. In this study, a series of uniaxial compressive tests on samples with different lamination orientation were undertaken using 3000 kN Tinius Olsen servo-controlled testing machine. The stress-strain curve of samples will be obtained through the laboratory testing. Stress-strain curve serves as the fundamental tool in understanding of the deformational behavior and engineering properties of rocks. Representative data on the fundamental rock properties like Poisson’s ratio, Young’s Modulus and strain at failure, particularly for sedimentary rocks that possess anisotropy behaviour, is essential for safe and economical design of civil engineering structures (i.e. tunnels, dams and slopes) associated with these type of rocks.